The identity of Bernard Mzeki from the formative history of the Anglican Church in Zimbabwe (1890-2013) : retracing his life, martyrdom and influence - Duncan, Graham A (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.